Effect of food simulating liquids on bulk-fill composites: A dynamic analysis approach / Ahmed Hesham Ahmed Mohamed Eweis - Ahmed Hesham Ahmed, Mohamed Eweis (2017)
Objective: To determine the effect of food simulating liquids on visco-elastic properties of bulk-fill restoratives using dynamic mechanical analysis. Material and Methods: Four dental composites were evaluated which included a conventional composite (Filtek Z350 [FZ]), two bulk-fill composites (Filtek Bulk-fill [FB] and Tetric N Ceram [TN]) and a bulk-fill giomer (Beautifil-Bulk Restorative [BB]). Test specimens (12 x 2 x 2mm) were fabricated using customized stainless steel molds. The specimens were light-cured, removed from their molds, finished, measured and randomly divided into six groups. The groups (n=10) were conditioned in the following mediums for 7 days at 37°C: air (control), artificial saliva (SAGF), distilled water, 0.02N citric acid, heptane, 50% ethanol-water solution. Specimens were then assessed using dynamic mechanical testing in flexural three-point bending mode and their respective mediums at 37°C and a frequency range of 0.1 to 10 Hz. The distance between the supports were fixed at 10mm and an axial load of 5N was employed. Data for elastic modulus, viscous modulus and loss tangent were subjected to ANOVA/Tukey’s tests at significance level p<0.05. Results: Significant difference in visco-elastic properties was observed between composite materials and conditioning mediums. With the exception of bulk-fill giomer restorative (BB), the highest elastic modulus was observed after conditioning in heptane. For BB, conditioning in air gave the highest elastic modulus. Excluding FB, the lowest elastic modulus was noted after exposure to ethanol. FB showed the lowest elastic modulus after conditioning in distilled water. No apparent trends were noted for viscous modulus. Excluding BB where exposure to citric acid gave the greatest values, iv loss tangent was the highest when the composites were conditioned in ethanol. For all materials, air and heptane had the lowest loss tangent values. Conclusion: The effect of food simulating liquids on the visco-elastic properties of the evaluated bulk-fill composites was material and medium dependent. The UDMA-based bulk-fill composite (FB), however, appeared to be more resistant to degradation effects of ethanol when compared to BisGMA-based conventional and bulk-fill composites.